PERANCANGAN MODEL STRATEGI PEMBELAJARAN DENGAN KONSEP VIRTUAL CLASSROOM - Agustin Setyorini (Informasi Interaktif, 2016)
The  design  model  of  learning  strategy  and  the  concept  of  virtual  classrooms have  the  main contribution of which implement the system administration tasks, materials and values for each task can be completed either by the student, the ability to rank students based on achievement of the task at hand so that the students have to do a better job and generate more value to be able to get a higher ranking and provide recommendations to the faculty about the outcome of the material assessment, assignment and quiz students based on student ratings to reward students with good results or otherwise for students with poor results.Key words: learning, concept, virtual classroom